Designing Interactive Audio-Visual Instructional Media Based On Value Clarification Technique (VCT) - Widodo, Urip; Ngadat, Ngadat; Subandi, Agus (Universitas Pendidikan Ganesha, 2021)
The minimum quality of instructional media which is completed with appropriate teaching method on Buddhist religious education subject impacts towards students’ learning achievement. This study aims to create and analyze the validity and feasibility of interactive audio-visual learning media based on VCT which focuses on material about Buddhist temples in Indonesia. The method used in this study is the research and development method by using ADDIE model. Data collection techniques were by giving questionnaires to media experts, material experts, teachers and students. Data analysis used was descriptive percentage and descriptive qualitative analysis. The results of the study indicate the instructional media is very feasible to use which can be seen from the questionnaire analysis with an average score of validation results by material experts is 82,5% which is included into very feasible, the results of media validation by media experts is 82,5% which is included into very feasible, the response of teachers towards instructional media compiled is 86,6% which is included into very feasible, and final result among 29 students response towards the media shows 25 students (86%) declare that the insructional media is very feasible meanwhile the rest 4 students (14%) argue that the media is feasible. In conclusion the learning media compiled are valid and very feasible to use in teaching Buddhist education about Buddhist temples in Indonesia.